Control strategy for AC-DC microgrid with hybrid energy storage under different operating modes - Tummuru, Narsa Reddy (2020)
In this paper, a control strategy is proposed for renewable-interfaced hybrid energy storage system (HESS) under grid connected/islanding conditions. A second harmonic based phased locked loop (PLL) is employed for effective synchronization/resynchronization of the microgrid system under contingency conditions. The operation and management of the microgrid system under both these modes are accomplished by an efficient adaptive power management algorithm. A quantitative analysis on the HESS performance is provided in order to investigate the effectiveness of the proposed approach. Further, small signal average models are derived to comment on the system stability. This approach address seamless transfer between the various sub-modes of the system along with additional services such as power quality enhancement and power dispatch between various sources. The effectiveness of the proposed scheme is verified by both simulation and experimental investigations.